MENINGKATKAN KEMAMPUAN MOTORIK KASAR ANAK USIA 3-4 TAHUN MELALUI KEGIATAN MELONCAT DENGAN PAPAN LONCAT di KB AZ ZAHRA - lisatus sobah; Prasetiya, Benny (Al-ATHFAL: Jurnal Pendidikan Anak, 2024)
This research aims to improve the gross motor skills of children aged 3-4 years through (jumping activities) using a diving board game (used cardboard APE) at KB Az Zahra. In the first semester of the 2023-2024 Academic Year. The research method used is the Kemmis and MC model Classroom Action Research method. Taggart, carried out in two cycles and each cycle consists of 5 meetings. Each step consists of 4 step, namely : a) planning, b) action, c) observation, d) reflection.Qualitative data analysis was carried out by observing the increase in the development of children’s gross motor ability criteria starting before the cycle until the second cycle. The criteria for children’s gross motor skills were set at 50%. Pre cycle data obtained an average of 57 %, then cycle I data obtained an average percentage of 79%, and cycle II data obtained an average of 83%. From the final results of cycle II, children obtained the highest results at 83%. Meanwhile, the one who got the lowest results with an average percentage of 46% was Raja. The conclusion is that the diving board game with jumping activities can improve the gross motor skills of children aged 3-4 years at KB Az Zahra. Keywords: Gross Motor Ability, Jumping Activies, Classroom Action Research